Short-Range Wireless Transmission in the 300 GHz Band Using Low-Profile Wavelength-Scaled Dielectric Cuboid Antennas - Yamada, Kazuki; Samura, Yuto; Minin, Oleg V.; Kanno, Atsushi; Sekine, Norihiko; Nakajima, Junichi; Minin, Igor V.; Hisatake, Shintaro (Frontiers in Communications and Networks, 2021)
A short-range terahertz (THz) wireless transmission in the 300 GHz band is demonstrated using low-profile wavelength-scaled dielectric transmitting and receiving cuboid antennas (DCAs). These dielectric cuboid antennas are made of polytetrafluoroethylene with dimensions of approximately 1.2 mm × 1.2 mm × 1.3 mm. The near-field pattern of a DCA at 300 GHz was measured using an electro-optic sensing technique, and its far-field pattern characterization was based on the near-field to far-field transformation. The measured antenna gain was 15.06 ± 0.06 dBi. By employing DCAs as transmitting and receiving antennas, a 17.5 Gbps data transmission rate at distances of approximately 200 and 50 mm with bit error rates of 3.31 × 10^−3 and 7.51 × 10^−7 respectively, is demonstrated. The proposed mesoscopic scale DCA is a promising antenna type in intra-device communications and Kiosk download applications for future mobile devices operating in the 300 GHz band.